MS-DOS literacy [videorecording] an introduction to MS DOS - Amee, Anthony; Hayes, Randolf; Mariano, Julius (Denver, Co. Aames Teleproductions, 1992)
Summary: Demonstrates the operating system and DOS commands.
Credits: Hosts, Kelly Hornbaker, Cynthia Deal; editor, Randolf Hayes.
Keywords: MS-DOS (Computer operating system).; MS-DOS (Computer file).